High Coercivity in MnAl Disc Prepared by Severe Plastic Deformation. Issue 3 (5th September 2019) - Si, Ping Zhan; Lim, Jung Tae; Park, Jihoon; Lee, Hak Hyeon; Ge, Hongliang; Lee, Hyunjong; Han, Sangho; Kim, Hyoung Seop; Choi, Chul Jin
Abstract : The low coercivity in MnAl alloys has become a barrier to develop high performance MnAl‐based magnets for more than five decades. Herein, a high room‐temperature coercivity of 0.59 T in MnAl disc is achieved by severe plastic deformation. The grain size of the MnAl decreases significantly when ε‐phase is transformed into τ‐phase and when the τ‐phase is severely deformed. The aging process enhances the magnetization of the deformed τ‐phase significantly and reduces the coercivity of the MnAl disc to 0.396 T. The magnetic domain structure of the severely deformed τ‐MnAl exhibits many pinning sites in the intergranular regions and within the domains, resulting in the high coercivity of the bulk samples. The deformation process produces locally oriented texture of τ‐phase. This study opens a window for development of MnAl‐based bulk magnet with high coercivity and enhanced remanence. Abstract : MnAl discs with high coercivity are prepared by high pressure torsion process. The grain size of MnAl decreases significantly when the ε‐phase is transformed into τ‐phase and when the τ‐phase is severely deformed. The aging process significantly enhances the magnetization of the deformed τ‐phase. This study opens a window for development of bulk MnAl with high coercivity and enhanced remanence.